Numerical investigation of cooling ability in heat-generating porous debris bed after severe accident in PWR - Xu, Junying; Dong, Xiaomeng; Zhang, Huiyong; Yun, Xiangyu; Zhang, Lei; Ye, Yuzhao; Liu, Xiang; Mo, Jinhong; Yang, Ming (Frontiers in Energy Research, 2023)
The porous debris bed formed after the severe accident is a porous structure composed of particles of different sizes. Due to the fission reaction in the debris bed, decay heat is released continuously. Therefore, the cooling ability should be investigated to determine the safety of the debris bed. In this paper, the two-phase conservation equations with closure correlations are proposed for the pool boiling phenomenon inside. For the flow resistance, the drag force between gas and liquid in continuous fluid is considered, and the flow resistance of solid to fluid in porous medium area is considered. The heat transfer model takes into account the heat transfer between solid liquid and solid gas, as well as the heat and mass transfer between gas and liquid. All the calculation are carried out based on the CFD method and the related models are written into the CFD calculation program in the form of User Defined Function (UDF). After the necessary validation of correlations proposed, the analysis and discussion are carried out around the effect of heating type, non-uniform distribution of structural parameters, and shape of geometry. Result shows the key effect of natural convection between the different boundary settings of heating type. The time series of strong natural convection formation and decay power heat are the determined factor for the position of boiling crisis. In addition, the limited power density is determined by the top half of debris bed. The increase of structural parameters and operating pressure would lead to a better cooling ability. For the shape of debris bed, regular cylinder is a better structure for the heat removal while the conical shape would reduce the limited power density a lot which is dangerous for the long-term cooling of the debris bed. The cooling ability would be better if a downcomer exists in the porous debris bed. The above three parts of the research are conducive to deepening the understanding of the process of the serious accident.